2007
DOI: 10.1179/174328007x160254
|View full text |Cite
|
Sign up to set email alerts
|

Application of electron backscatter diffraction to the study of phase transformations

Abstract: 615 ref. biblioInternational audienceThe application of the electron backscatter diffraction technique to the investigation of phase transformations is reviewed. The wide variety of results obtained using this technique is illustrated and discussed, focusing on thermodynamics and kinetics of phase transformations, solidification, solid state phase transformations, environmentally assisted reactions and thin film deposition. Emphasis is also placed on two rapidly growing developments: coupling electron backscat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 490 publications
3
47
0
2
Order By: Relevance
“…The electron back-scattered Kikuchi diffraction patterns (EBKDP) are detected in SEM simply from bulk alloy specimens, rather than by using the transmission electron microscopy (TEM). 4,5) The EBSD can also facilitate …”
Section: Methodsmentioning
confidence: 99%
“…The electron back-scattered Kikuchi diffraction patterns (EBKDP) are detected in SEM simply from bulk alloy specimens, rather than by using the transmission electron microscopy (TEM). 4,5) The EBSD can also facilitate …”
Section: Methodsmentioning
confidence: 99%
“…The EBSD can also facilitate evidence of phase transformation by discriminating between phases having close or even identical crystal structures. [25][26][27][28] An EBSD examination was carried out on the Leo 1530 FESEM using a commercially available software from HKL Technology APS Ltd. (Oxford, UK). In performing EBSD, the specimens were tilted at 70 degrees.…”
Section: Methodsmentioning
confidence: 99%
“…The advent of electron back-scattered diffraction (EBSD) 71,72 made it possible to examine the hypothesis that the good toughness of an acicular ferrite microstructure has its origin in the crystallographic dispersal of plates of ferrite. A marvellous paper by Gourgues et al 73 showed experimentally that highly misoriented plates formed from the same inclusion, so that the boundaries between plates represent formidable barriers to crack propagation.…”
Section: Guest Editorialmentioning
confidence: 99%